1992
DOI: 10.1038/bjc.1992.26
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic comparison of intravenous versus intra-arterial folinic acid

Abstract: Summary Recent clinical trials have suggested that a combination of folinic acid and 5-fluorouracil (5-FU) may improve response rates and survival in patients with advanced colorectal cancer. However, this regimen has been complicated by potentially life threatening toxicity. Regional delivery of folinic acid via a hepatic artery catheter might be expected to reduce systemic exposure and subsequent adverse effects.The present study compared the pharmacokinetic profiles of intravenous and intra-hepatic arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Short-term folate kinetics often have been examined using a single folate dose administered orally or intravenously followed by serial measurement of either total folate or individual folate forms in serum or plasma (e.g., 1,10,48,53,66,90). The need for relatively large doses to induce a consistently measurable change in plasma folate concentration is a limitation of protocols involving short-term plasma response (3,63), although such studies have relevance to clinical therapies.…”
Section: Unlabeled Folatesmentioning
confidence: 99%
“…Short-term folate kinetics often have been examined using a single folate dose administered orally or intravenously followed by serial measurement of either total folate or individual folate forms in serum or plasma (e.g., 1,10,48,53,66,90). The need for relatively large doses to induce a consistently measurable change in plasma folate concentration is a limitation of protocols involving short-term plasma response (3,63), although such studies have relevance to clinical therapies.…”
Section: Unlabeled Folatesmentioning
confidence: 99%
“…Further evidence suggests that modulation of regional 5-FU administration with folinic acid might confer significant therapeutic advantage (Anderson et al, 1991). Unfortunately, regional administration of folinic acid precipitated hepatic artery occlusion in some patients, while in previous studies with regional FUDR (Kemeny et al, 1989b), it had been shown to potentiate the risk of biliary sclerosis.…”
Section: Pharmacological Rationale For Regional Chemotherapymentioning
confidence: 99%
“…The recommended dose of hepatic arterial 5-FU as a 24h infusion when given in combination with a fixed dose of intravenous folinic acid (400 mg M-2) once per week (Anderson et al, 1992) was found to be 1.5 gm 2 week-'. At this dosage, neither myelosuppression nor hepatoxicity was apparent, while dose escalation to 2.0 g m2 week-' 5-FU was associated with WHO grade 3/4 diarrhoea and vomiting.…”
Section: Pharmacological Rationale For Regional Chemotherapymentioning
confidence: 99%
“…In vitro studies have suggested that a minimum extracellular L-folate concentration of 10 Ismol 1-' is required to maximise modulation of 5-FU thymidylate synthase inhibition (Evans et al, 1981). A 2 h intravenous infusion of 200 mg m-2 would be expected to provide such a satisfactory plasma folinic acid concentration (Anderson et al, 1991). However, 24h intravenous infusions of 500mgm-2 folinic acid fail to provide adequate plasma concentrations of folinic acid (Rustum, 1989).…”
Section: Toxicitymentioning
confidence: 99%
“…We have shown in a series of previous pharmacokinetically guided studies that 24 h intraarterial infusion of 5-FU confers a significant pharmacological advantage relative to intravenous infusions or intra-arterial bolus administration (Goldberg et al, 1990). Regional administration of folinic acid is also associated with a statistically significant reduction in systemic exposure compared with the intravenous route but this apparent pharmacokinetic advantage has been offset by the potential for hepatic artery catheter thrombosis with this drug (Anderson et al, 1991).…”
mentioning
confidence: 99%